Historisitas Iklan Layanan Kereta Api Eendaagsche Expres di Media Cetak Tahun 1929-1942 - Anwari, Ikhsan Rosyid Mujahidul; Rayhaan, Rafif (Historia Madania: Jurnal Ilmu Sejarah, 2024)
This research aims to explain the development of advertising from year to year on the Staatsspoorwegen (SS) Eendaagsche Expres train service. Apart from that, it will also explain SS's efforts to operate the Eendaagsche Expres train. An explanation of the operational and advertising developments of Eendaagsche Expres can be achieved using historical research methods, including: heuristics or collections of written sources in the form of archives and images; source verification; interpretation; and historiography or historical writing. By using this method, the results were obtained that at the end of the 1920s to the beginning of the 1940s there was a trend in the use of advertising designs that was different from before. Like there is a visualization of ornaments or a picture of a train. Then there is also the evolution of the elements in the advertisement itself. The advertising analysis used in this research focuses on the development of headlines, body copy and slogans. The development of advertising design also occurred in the Eendaagsche Expres advertising publication, which experienced rapid development until the end of its operational period in 1942.